Debt, Deficits, and Finite Horizons - Blanchard, Olivier J. (Journal of Political Economy, 1985)
Many issues in macroeconomics, such as the level of the steady state interest rate, or the dynamic effects of government deficit finance, depend crucially on the horizon of economic agents. This paper develops a simple analytical model in which such issues can be examined and in which the horizon of agents is a parameter which can be chosen arbitrarily.The first three sections of the paper characterize the dynamics and steady state of the economy in the absence of a government. The focus is on the effects of the horizon index on the economy. The paper clarifies in particular the separate roles of finite horizons and declining labor income through life in the determination of steady state interest rates.The next three sections study the effects and the role of fiscal policy.The focus is on the effects of deficit finance both in closed and open economies. The paper clarifies the respective roles of government spending, deficits and debt in the determination of interest rates.